2017
DOI: 10.1177/0963689717742157
|View full text |Cite
|
Sign up to set email alerts
|

Decellularization and Solubilization of Porcine Liver for Use as a Substrate for Porcine Hepatocyte Culture

Abstract: Biologic substrates, prepared by decellularizing and solubilizing tissues, have been of great interest in the tissue engineering field because of the preservation of complex biochemical constituents found in the native extracellular matrix (ECM). The integrity of the ECM is critical for cell behavior, adhesion, migration, differentiation, and proliferation that in turn affect homeostasis and tissue regeneration. Previous studies have shown that various processing methods have a distinctive way of affecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 92 publications
4
58
0
Order By: Relevance
“…Human primary HEPs are known to lose their morphology and metabolic functions within the first couple of days of in vitro culture [8]. Recent studies suggest that animal-derived liver ECM, when used as a coating or media supplement in 2D cultures, can favorably affect the production of albumin and urea in rat and porcine primary hepatocytes [16][17][18]. We sought to investigate whether a HL-ECM coating could similarly affect the functionality of thawed human primary HEPs and represent a better alternative than the traditionally used rat tail collagen I coating.…”
Section: Evaluation Of Solubilized Hl-ecm For Primary Human Liver Celmentioning
confidence: 99%
See 1 more Smart Citation
“…Human primary HEPs are known to lose their morphology and metabolic functions within the first couple of days of in vitro culture [8]. Recent studies suggest that animal-derived liver ECM, when used as a coating or media supplement in 2D cultures, can favorably affect the production of albumin and urea in rat and porcine primary hepatocytes [16][17][18]. We sought to investigate whether a HL-ECM coating could similarly affect the functionality of thawed human primary HEPs and represent a better alternative than the traditionally used rat tail collagen I coating.…”
Section: Evaluation Of Solubilized Hl-ecm For Primary Human Liver Celmentioning
confidence: 99%
“…There is in this regard a growing interest in the use of liver ECM derivatives as a coating, supplement or substrate to provide liver cells with an environment that presents structural, mechanical and biochemical characteristics closer to their native microenvironment. However, studies so far have primarily focused on evaluating the impact of liver ECM derivatives on the culture of immortalized cell lines or animal-derived cells and have collectively returned ambiguous results [13][14][15][16][17][18]. To our knowledge, the composition of human liver-specific ECM (HL-ECM) and its potential impact on the function and phenotype of the main human liver cell populations has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The very next alternative that researchers explored was to obtain tissue source from other species and use its matrix as a bioink for tissue development [23]. The concept of using other species (porcine) tissue as a source of material for humans emerged due to the anatomical and physiological similarities between both the species [83,84]. Apart from the cellular content, organs are rich in the noncellular component, i.e., ECM [85].…”
Section: Importance Of Xenografts In Decm-based Bioprintingmentioning
confidence: 99%
“…Evidence points out that the preserved components of ECM differ in number and type depending on the method of decellularization. While in a method the greater amount of components is preserved, however, the substrates required to support hepatic cells or tissue carrying stem cells such as fibronectin, collagen and GAGs may be also excluded [120]. Experiments showed endogenous cytokines and growth factors attached to side chains of GAGS either can be conserved after decellularization [17].…”
Section: Hepatic Differentiation Of Various Stem Cells On Decellularimentioning
confidence: 99%
“…Experiments showed endogenous cytokines and growth factors attached to side chains of GAGS either can be conserved after decellularization [17]. In a very recent study, mass spectrometric analysis revealed that the amount of ECM proteins in a liver decellularized by deoxycholate were significantly higher than those decellularized by ammonium hydroxide, but the retained ECM proteins in the latter mainly were fibronectin, collagen (types 1 and 4) and proteoglycans, participating in cell attachment, survival, growth and hepatic differentiation [120]. Since the type and amount of the material content of scaffold affect the orientation of stem cells toward the hepatic lineage, quantitative and qualitative evaluation of decellularized scaffolds component appears to be essential prior to recellularization [120].…”
Section: Hepatic Differentiation Of Various Stem Cells On Decellularimentioning
confidence: 99%